2005
DOI: 10.1042/cs20040175
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of critical lower limb tissue hypoxia by coupling chemical and optical techniques

Abstract: It has been a long-term goal to develop non-invasive methods that can detect critical levels of tissue hypoxia to help in the management of chronic lower limb ischaemia. In the present study, skeletal muscle oxygenation was measured using a new Clark-type TCPO2 [transcutaneous PO2 (partial pressure of O2)]/PCO2 (partial pressure of CO2) monitoring system and optical NIRS (near-infrared spectroscopy) at graded levels of hypoxaemia using a rabbit model (n=6). The TCPO2/PCO2 probe was placed on the shaved hindlim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In addition to the advantages of this method discussed above, we can use the described equations as a simulation tool to explain cases of high or low deoxygenation during perturbations and/or recovery of reoxygenation. This is very important in the diagnosis of vascular disease and myopathy [ 3 , 27 , 31 - 33 ], as well as when studying different types of muscle fibers and metabolic processes involved [ 30 ]. Examples of simulation that can be used to interpret the reoxygenation kinetic in the ischemia studies, as well as recovery from muscle exercise protocols, are demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the advantages of this method discussed above, we can use the described equations as a simulation tool to explain cases of high or low deoxygenation during perturbations and/or recovery of reoxygenation. This is very important in the diagnosis of vascular disease and myopathy [ 3 , 27 , 31 - 33 ], as well as when studying different types of muscle fibers and metabolic processes involved [ 30 ]. Examples of simulation that can be used to interpret the reoxygenation kinetic in the ischemia studies, as well as recovery from muscle exercise protocols, are demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…61 Thus, T C PO 2 is a more sensitive index to evidence of decrease in local blood flow than T C PCO 2 . Conversely, increase in T C PCO 2 is a more specific index of a significant decrease in blood flow and, in some studies, has been shown to more specifically predict amputation than T C PO 2 .…”
Section: Transcutaneous Carbon Dioxide Pressure Measurementsmentioning
confidence: 99%
“…However, due to the greater skin diffusion capability of CO 2 compared to O 2 , alterations in T C PCO 2 appear later than in T C PO 2 when skin blood flow decreases. 61 Thus, T C PO 2 is a more sensitive index to evidence of decrease in local blood flow than T C PCO 2 . Conversely, increase in T C PCO 2 is a more specific index of a significant decrease in blood flow and, in some studies, has been shown to more specifically predict amputation than T C PO 2 .…”
Section: Transcutaneous Carbon Dioxide Pressure Measurementsmentioning
confidence: 99%
“…We also like to mention that additional to SpO 2 , the transcutaneous partial pressure of oxygen (TcPO 2 ) is another vascular tool commonly used in vascular medicine to reflect local arterial blood flow and skin oxygenation. This tool has been described as a potential predictor of cardiovascular events and blood flow before and after revascularization in patients with peripheral artery disease, including in patients with conditions such as end-stage renal disease and diabetes [23][24][25].…”
Section: Discussionmentioning
confidence: 99%